ETV2 and VEZF1 interaction and regulation of the hematoendothelial lineage during embryogenesis - Das, Satyabrata; Gupta, Vinayak; Bjorge, Johannes; Shi, Xiaozhong; Gong, Wuming; Garry, Mary G.; Garry, Daniel J. (Frontiers in Cell and Developmental Biology, 2023)
Ets variant 2 (Etv2), a member of the Ets transcription factor family, has an essential role in the formation of endothelial and hematopoietic cell lineages during embryonic development. The specificity and function of ETS transcription factors are, in part, contingent upon their interacting proteins. However, there are very few studies exploring the coordinated interplay between ETV2 and its interacting proteins that regulate mesodermal lineage determination. In order to identify novel ETV2 interacting partners, a yeast two-hybrid analysis was performed and the C2H2 zinc finger transcription factor VEZF1 (vascular endothelial zinc finger 1) was identified as a binding factor, which was specifically expressed within the endothelium during vascular development. To confirm this interaction, co-immunoprecipitation and GST pull down assays demonstrated the direct interaction between ETV2 and VEZF1. During embryoid body differentiation, Etv2 achieved its peak expression at day 3.0 followed by rapid downregulation, on the other hand Vezf1 expression increased through day 6 of EB differentiation. We have previously shown that ETV2 potently activated Flt1 gene transcription. Using a Flt1 promoter-luciferase reporter assay, we demonstrated that VEZF1 co-activated the Flt1 promoter. Electrophoretic mobility shift assay and Chromatin immunoprecipitation established VEZF1 binding to the Flt1 promoter. Vezf1 knockout embryonic stem cells had downregulation of hematoendothelial marker genes when undergoing embryoid body mediated mesodermal differentiation whereas overexpression of VEZF1 induced the expression of hematoendothelial genes during differentiation. These studies provide further insight into the co-regulation of the hemato-endothelial lineage development via a co-operative interaction between ETV2 and VEZF1.